ASSESSING THE EFFECT OF ONLINE LEARNING SERVICE QUALITY ON CUSTOMER RETENTION THROUGH CUSTOMER SATISFACTION AS MEDIATION VARIABLE IN THE CULINARY STUDY PROGRAM BACHELOR DEGREE DURING THE COVID-19 PANDEMIC - Leoparjo, Fabiola; Harianto, Eric; Ilyas, Gunawan Bata; Hasanah, Yulia Nur; Mas’ud, Riduan (Jurnal Aplikasi Manajemen, 2023)
This quantitative study explores the relationship between online learning service quality, customer satisfaction, and customer retention in the Culinary Study Program during the Covid-19 pandemic. Using data from 217 students in a private university, specifically in Surabaya. The analysis employed in this study is Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationship between the research variables, including the measurement model (outer model) for validity and reliability testing, and the structural model (inner model) for hypothesis testing and mediation analysis. The research reveals a significant direct effect of online learning service quality on customer satisfaction. Higher levels of service quality positively impact customer satisfaction, aligning with previous research in e-learning contexts. Additionally, the study establishes a significant indirect effect of online learning service quality on customer retention through customer satisfaction as a mediation variable. Higher customer satisfaction levels lead to increased customer retention in the Culinary Study Program. These findings offer insights for educational institutions to enhance service quality and customer satisfaction, focusing on dimensions such as content, system functionality, and interaction quality. Implementing strategies to prioritize student satisfaction can improve online learning effectiveness during challenging times like the Covid-19 pandemic. Overall, this study contributes to the knowledge of online learning service quality, customer satisfaction, and customer retention, emphasizing the importance of high-quality online learning experiences for student satisfaction and retention in the Culinary Study Program during the Covid-19 pandemic.